LEMBAGA KOMUNITAS LOKAL (STUDI TENTANG PERANNYA DALAM PEMBERDAYAAN MASYARAKAT KELURAHAN DI KOTA SEMARANG 2016 ) - Suharto Suharto (SOSIO DIALEKTIKA : JURNAL ILMU SOSIAL HUMANIORA, 2018)
Institutional Local Communities are local community institutions that are built andstrengthened according to the needsof the community in a process of social transformationthat is rooted, acknowledged and accepted by the community. The role of local communityinstitutions in community empowerment is one of them participate in poverty reductionprogram which includes allactivities of empowerment of village / village community. In theempowerment of the community the main target is the powerless community (poor) in thebroadest sense and in fact most of the poor are urban community.In the communityempowerment program hasalways been encouraged to be more pro poor and give moreopportunities to the role of the community in community empowerment, especially the poor inKelurahan.The existence of local community institutions in accordance with the interests andneeds of these communities can be a driver of social capital for the process of socialtransformation from the condition of a powerless society into a powerless society, self-reliantand civil society who aspired together. The role of local community institutions BKM, LPMKand PKKcommunity empowerment Muktiharjo Kidul Urban Village that all institutionsparticipate in poverty alleviation urban village communityand the role of each localcommunity institutions in doing every community empowerment activities of the village tendto support and try with the aim that the community more empowered, independent andprosperous.Keywords: Local Community Institution, Community Empowerment